LEVEL OF STRESSOR TENSION AND EVALUATION OF QUALITY OF LIFE IN PATIENTS WITH HYPERTENSION - Podolsky, A.V.; Steblyuk, V.V. (World of Medicine and Biology, 2014)
Was analysed the level of psychoemotional tension in patients with hypertension . At 64.46 % of patients with hypertension was observed elevated levels of psychoemotional tension. The maximal expression of neuroendocrine and neurovegetative reactions were found among patients with the syndrome of psychoemotional tension and hypertension I stage. Among patients with a syndrome of psychoemotional tension and hypertension stage II was found reduction in cortisol and adrenocorticotropic hormone normalization due to the development of protective and adaptive reactions. In patients with a syndrome of emotional stress and hypertension stage III was found depletion stage of adaptation reserves inherently to the long-term chronic stress.